Learner Satisfaction in BIPA Programs: A Multi-Class Survey Analysis - Benny Krisbiantoro (Media Publikasi Cendekia Indonesia, 2026)
Learner satisfaction plays a crucial role in evaluating the effectiveness of language programs, including Bahasa Indonesia for Foreign Speakers (BIPA). This study investigated learner satisfaction and identified factors influencing their experiences in a BIPA program conducted at the Indonesian Embassy (KBRI) in Washington, DC. A mixed-method approach was employed with 117 learners across multiple classes. Quantitative data were analyzed using descriptive statistics and correlation analysis, while qualitative responses from open-ended questions were examined through thematic analysis. Findings indicated high satisfaction regarding teaching quality and classroom interaction, whereas multimedia use and opportunities for authentic language practice required improvement. The study highlighted the importance of adaptive teaching, authentic materials, and learner-centered approaches in enhancing BIPA programs. These results offer practical implications for program development and contribute to the growing research on BIPA.